Genetic Testing in Prion Disease: Psychological Consequences of the Decisions to Know or Not to Know - Schwartz, Mathias; Brandel, Jean-Philippe; Babonneau, Marie Lise; Boucher, Christilla; Schaerer, Elodie; Haik, Stephane; Laplanche, Jean Louis; Gargiulo, Marcela; Durr, Alexandra (Frontiers in Genetics, 2019)
Purpose: Presymptomatic testing for susceptibility to genetic prion diseases is often delivered in difficult circumstances, as the index case is often dying when a genetic diagnosis is obtained. Since test requests in these diseases are very rare, the factors underlying decisions of relatives to be tested or not and the long-term psychological consequences are not reported. Methods: We contacted subjects who had consulted between 2004 and 2017 because a relative carried a pathological PRNP variant. Standardized psychological scales and semistructured interviews were proposed. Results: We did contact 19 of the 30 subjects who had consulted: 6 of 10 who did not undergo testing, 10 of 12 noncarriers, and 3 of 8 mutation carriers. Anxiety rates were high and similar between noncarriers and untested subjects. Conclusions: Living in a family with inherited prion disease produced psychological burden, regardless of the decision to undergo testing and its results. Decisions in favor of being testing did not allow relief of anxiety about the family disease. The dilemmatic decision not to know remained a burden to be coped with. Genetic counseling procedures should take into account all these situations, even that of noncarriers and that of untested.